A mitochondrial-targetable fluorescent probe based on high-quality InP quantum dots for the imaging of living cells. (July 2022) - Zhang, Yanbin; Qiao, Lu-Lu; Zhang, Zhi-Qiang; Liu, Yong-Fang; Li, Lin-Song; Shen, Huaibin; Zhao, Mei-Xia
Graphical abstract: The InP QD probes has extremely low toxicity, excellent photostability, superior fluorescence properties and favorable biocompatibility. Considering the trend of Cd-free QDs in biological applications, the research based on InP QDs as mitochondrial probes is interesting for the related researchers and benefit many potential applications of Cd-free QDs in biology. Highlights: Synthesis of red high-quality InP core/shell quantum dots based on aminophosphorus precursors. The aqueous InP quantum dots modified with polyethyleneimine can maintain the initial optical properties. Modified InP quantum dots can be used as a universal mitochondrial probe. These InP quantum dots probes with excellent biocompatibility and photochemical stability. Abstract: Numerous cellular functions are closely reliant on mitochondria and so the capability to conduct long-term stable studies of their activity is of great importance. However, current commercial mitochondrial probes are severely limited in their ability to trace mitochondria due to their inherently poor stability. Here, for the first time, we designed a novel mitochondrial fluorescent probe using InP quantum dots (QDs) as a fluorescent master and skillfully combined with  (3-carboxypropyl)triphenylphosphine (TPP) for specific recognition. The bespoke InP QDs probes described here exhibited clear advantages, including simple and low-cost synthesis, high quantum yields, extremely low toxicity, good biocompatibility, and excellent photochemical stability, thus representing a versatile, novel mitochondrial fluorescent probe, particularly suitable in applications traditionally undertaken by Cd-based QDs in biological fields.